Eksistensi Pidana Mati dalam Sistem Peradilan Pidana Indonesia Perspektif Hak Asasi Manusia - Sukedi, Mochamad (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The existence of human rights is a concept that in principle is inherent in the existence and life of humans, human rights actually have a long history in which history can be traced from daily intercourse between humans. The international world knows the form of capital punishment is a type of crime that is very controversial and heaviest imposed on the perpetrators of crime so that it always raises a variety of pros and cons opinions in it. Based on this, the purpose of this paper is to find out and understand the basic legal arrangements for the death penalty in Indonesia and the application of capital punishment in the perspective of human rights. This research uses normative legal research. The death penalty is a very old type of crime that may even be as old as the existence of humanity itself. Capital punishment is the most severe type of criminal offenses of all types of basic crimes, so that capital punishment sanctions constitute a threat imposed on the perpetrators of serious crimes that have been decided by the court. In the international worldview, capital punishment is one of the most controversial forms of crime of all types of criminal sanctions in the criminal justice system in force in the world. Regarding law enforcement applied in Indonesia itself, it still applies the provisions of criminal sanctions in the Criminal Code (KUHP) and there is also listed in the Law outside the Criminal Code. Keberadaan hak asasi manusia merupakan suatu konsep yang pada prinsipnya melekat pada keberadaan dan hidup manusia, hak asasi manusia sesungguhnya memiliki sejarah panjang yang mana sejarah tersebut dapat ditelusuri dari pergaulan sehari-hari antarmanusia. Dunia Internasional mengenal bentuk pidana mati adalah merupakan jenis pidana yang sangat kontroversial dan terberat dijatuhkan kepada pelaku kejahatan, sehingga selalu menimbulkan berbagai opini pro-kontra di dalamnya. Berdasarkan hal tersebut maka tujuan dalam penulisan ini yaitu untuk mengetahui dan memahami tentang pengaturan dasar hukum pidana mati di Indonesia serta penerapan pidana mati dalam perspektif hak asasi manusia. Penelitian ini menggunakan jenis penelitian hukum normatif. Sanksi pidana mati merupakan salah satu jenis pidana yang sangat tua bahkan mungkin sama tuanya dengan keberadaan umat manusia itu sendiri. Sanksi pidana mati yaitu jenis pidana yang paling berat dari segala jenis pidana pokok, sehingga sanksi pidana mati merupakan ancaman yang dikenakan kepada pelaku kejahatan berat yang telah diputus oleh pengadilan. Dalam pandangan dunia internasional, pidana mati adalah salah satu jenis bentuk pidana paling kontroversial dari semua jenis sanksi pidana dalam sistem peradilan pidana yang berlaku di dunia. Mengenai penegakan hukum yang diterapkan di Indonesia sendiri masih menerapkan ketentuan sanksi pidana dalam Kitab Undang-Undang Hukum Pidana (KUHP) dan ada pula yang dicantumkan di dalam Peraturan Perundang-undangan di luar KUHP.